Sirtuin 5 regulates acute myeloid leukemia cell viability and apoptosis by succinylation modification of glycine decarboxylase - Zhang, Jun; Luo, Cheng; Long, Haiying (Open life sciences, 2024)
Acute myeloid leukemia (AML) is a blood system malignancy where sirtuin 5 (SIRT5) is abnormally expressed in AML cell lines. This study aimed to investigate the SIRT5 effects on the viability and apoptosis of AML cell lines. The mRNA and protein expression levels of succinylation regulatory enzyme in clinical samples and AML cell lines were detected by real-time quantitative polymerase chain reaction and western blotting while cell viability was measured using cell counting kit-8 assay. The apoptosis rate was assessed with flow cytometry. The interaction between SIRT5 and glycine decarboxylase (GLDC) was determined by co-immunoprecipitation and immunofluorescence staining techniques. Results indicated higher mRNA and protein expression levels of SIRT5 in clinical AML samples of AML than in normal subjects. Similarly, cell viability was inhibited, and apoptosis was promoted by downregulating SIRT5, in addition to inhibition of SIRT5-mediated GLDC succinylation. Moreover, rescue experiment results showed that GLDC reversed the effects of SIRT5 knockdown on cell viability and apoptosis. These results, in combination with SIRT5 and GLDC interactions, suggested that SIRT5 was involved in mediating AML development through GLDC succinylation. SIRT5 inhibits GLDC succinylation to promote viability and inhibit apoptosis of AML cells, suggesting that SIRT5 encourages the development of AML.